Binaphthyl-incorporated π-conjugated polymer/gold nanoparticle hybrids: a facile size- and shape-tailored synthesis. Issue 109 (11th November 2016) - Song, Sun Gu; Ha, Seonggyun; Seo, Kyeong-Bae; Lee, Jookyeong; Choi, Tae-Lim; Premkumar, Thathan; Song, Changsik
Abstract : Size and shape of in situ synthesized polymer/gold nanocomposites were controlled by the solvents utilized and the molecular weights of the binaphthyl-incorporated π-conjugated polymers. Abstract : Size- and shape-tailored metal nanoparticles and π-conjugated polymer hybrids are applied in various fields such as surface-enhanced Raman scattering, sensors, heterogeneous catalysis, solar cells, and memory devices. For such applications, it is important to precisely control the morphology of the polymer–metal nanoparticle hybrids. In our study, we utilized binaphthyl-incorporated conjugated polymers to simultaneously reduce auric ions (Au 3+ ) to gold nanoparticles and stabilize them, which resulted in nanoparticle and π-conjugated polymer hybrids. Interestingly, we found that the size and shape of the gold nanoparticles were controlled by the solvents utilized and molecular weights of the binaphthyl-containing π-conjugated polymers. We attributed this to the difference in the coverage of the gold nanoparticle facets by the polymers, which was dictated by the conformation of the polymers and reduction rates in different solvents. In addition, the hybrid materials showed enhanced electrochemical properties compared to the polymers.